High-performance eco-friendly Ni Cu/bamboo activated carbon catalysts for oxidative desulfurization of high-concentration DBT - Haerani, St.; Trisunaryanti, Wega; Triyono; Santoso, Imam; Purbonegoro, Jason; Wangsa (Communications in Science and Technology, 2025)
This study investigated how the metal impregnation method affects the oxidative desulfurization (ODS) of dibenzothiophene (DBT) using H2O2 over Ni–Cu catalysts supported on bamboo-derived activated carbon. Catalysts with 1% and 2% Ni–Cu were prepared via simultaneous impregnation, while the effect of sequence was evaluated by comparing simultaneous and sequential impregnation (2%Ni-2%Cu/AC and 2%Cu-2%Ni/AC). The 2%Ni-2%Cu/AC catalyst was identified as the best catalyst, with a surface area of 802.36 m2/g, average pore diameter of 2.4761 nm, and total acidity of 3.1239 mmol/g. This catalyst achieved the highest DBT reduction of 90.81% under optimal conditions (0.2 g catalyst weight, 60 minutes, 40 °C, and 0.66 mL H2O2), confirming that the sequential impregnation route significantly enhances catalytic performance. In conclusion, the impregnation sequence in designing highly efficient desulfurization catalysts is important due to spray impregnation resulting in higher surface area, acidity, and catalytic activity compared to the simultaneous impregnation method.